Pengaruh Kesiapan Belajar, Motivasi, Efikasi Diri Terhadap Konsep Diri, Dan Prestasi Siswa Di Madrasah Aliyah Negeri 2 Model Medan - Hadijaya, Yusuf; Kalsum, Umi; Satriyadi, Satriyadi; Wasiyem, Wasiyem; Syahri, Putri (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Student achievement is influenced by a number of interrelated factors. Good learning readiness provides a strong foundation for students to study effectively. High motivation encourages students to involve themselves in the learning process with enthusiasm. Strong self-efficacy strengthens students' belief in their ability to achieve good learning achievements. Meanwhile, a positive self-concept influences students' perceptions of their abilities and provides additional motivation to achieve higher achievements. This research is a causal expose facto research, because the purpose of this research is to reveal the causal relationship between research variables, namely: learning readiness, motivation, self-efficacy, self-concept, and learning achievement. The results of the study are student learning readiness, high learning motivation and student self-efficacy. Student learning readiness is something that needs to be considered starting from their mental, emotional and cognitive readiness. In addition, motivation is also an important part in forming a strong self-concept by arousing student interest and enthusiasm, maintaining student curiosity, and giving praise or rewards for their success.Keyword: Readiness to Learn, Motivation, Self-Efficacy, Self-Concept, Student Achievement